Guidance for evidence-informed policies about health systems: rationale for and challenges of guidance development. - Xavier Bosch-Capblanch; John N Lavis; Simon Lewin; Rifat Atun; John-Arne Røttingen; Daniel Dröschel; Lise Beck; Edgardo Abalos; Fadi El-Jardali; Lucy Gilson; Sandy Oliver; Kaspar Wyss; et al. (PLoS Medicine, 2012)
In the first paper in a three-part series on health systems guidance, Xavier Bosch-Capblanch and colleagues examine how guidance is currently formulated in low- and middle-income countries, and the challenges to developing such guidance.